(3GdefGgL GdYdejI dJWhjQ GdcaGAGJ GdegfjI (B/s - (3KGHJj, GdMHjHs ((3JdeSGf(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2017)
-(3efgLjI JWhjQ GdcaGAGJ Ydi eSJhi GdJfXjej (B:(3GdTQhW GdeSHbI dJfajP efgLjI JWhjQ GdcaGAGJ (B-(3GdeMGhQ GdcHQi defgLjI JWhjQ GdcaGAGJ GdJfXjejI (B-(3GdGOhGJ GdYdejI hGdJbfjI dJSjjQ hJWhjQ GdcaGAGJ (B-(3efgLjI JWhjQ GdcaGAGJ Ydi GdeSJhi GdaQOj (B:(3GdJchjf aj GdhSW Gdegfj (B-(3efs
(3HHdjhZQGajG(B:(3U(B.105s
Keywords: (3EOGQI GdCaQGOs; (3GdcaGFI GdGOGQjIs